Roget's thesaurus - Roget, Peter Mark (Penguin Books, 1998)
Roget's Thesaurus ranks as one of the greatest English language reference works, used for generations by anyone looking for help in order to write a letter, prepare a speech, solve a crossword, or write any manner of prose or poem. Its sales now exceed 32 million copies. This edition has been revised and updated to include all the latest buzzwords and phrases. In addition this new edition of Roget contains useful panels of additional information that include such nuggets of information as signs of the zodiac and the origins of familiar quotations that have become an integral part of our everyday language.